Monitoring the intramolecular charge transfer process in the Z907 solar cell sensitizer: a transient Vis and IR spectroscopy and ab initio investigation1. Issue 33 (7th September 2015) - Azzaroli, Nicolò; Lobello, Maria Grazia; Lapini, Andrea; Iagatti, Alessandro; Bussotti, Laura; Di Donato, Mariangela; Calogero, Giuseppe; Pastore, Mariachiara; De Angelis, Filippo; Foggi, Paolo
<x xml:space="preserve">Abstract</x> The excited state dynamics of Z907 in solution and on semiconductor substrates has been studied with ultrafast UV/Vis and IR spectroscopy and DFT/TDDFT calculations.